Analyzing the unity of the world around me in the virtual kindergarten in light of promoting cultural identity - Bawazeer, Salwa AbuBakr; Althobyani, Elham AbdulAziz; Alamiri, Afaf Rasheed; Alhassan, Jomanah Faisal; Alzharani, Waad Saeed; Albogami, Alhanouf Majed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the concept of cultural identity and its importance for the child, determine its dimensions, and identify the contents of it in the unity of the world around me presented in the virtual kindergarten in the Kingdom of Saudi Arabia. The researchers used the descriptive analytical approach represented by the method of content analysis, using the content analysis card that was prepared by the researchers in the light of the dimensions and pivots of cultural identity. It consists of three main dimensions, from which (15) sub-indicators are branched, whose validity and reliability have been confirmed. The findings of the research concluded with a general result that there is a discrepancy between a medium to a decrease in the degree of inclusion of the content of the unity of the world around me in the virtual kindergarten in the kingdom of Saudi Arabia for the dimensions of cultural identity, and the percentages varied from one dimension to another, where the heritage dimension ranked first in the inclusion with a percentage of (52%) with a medium degree of inclusion, while the religious dimension ranked second with a percentage of (29%) and a low degree of inclusion. As for the linguistic dimension, it ranked the last with a percentage of (19%) and a more low degree of inclusion. In light of these findings, proposals were made to include the content of the unity of the world around me in the virtual kindergarten for the dimensions of cultural identity in a large degree. Accordingly, the recommendations were to update the unity of the world around me in the virtual kindergarten for the kindergarten stage in the Kingdom of Saudi Arabia in light of its inclusion of the dimensions of cultural identity in a large degree.
Keywords: Cultural Identity; Unit Analysis; Virtual Kindergarten